Small molecule inhibitors reveal an indispensable scaffolding role of RIPK2 in NOD2 signaling. (19th July 2018) - Hrdinka, Matous; Schlicher, Lisa; Dai, Bing; Pinkas, Daniel M; Bufton, Joshua C; Picaud, Sarah; Ward, Jennifer A; Rogers, Catherine; Suebsuwong, Chalada; Nikhar, Sameer; Cuny, Gregory D; Huber, Kilian VM; et al.
Abstract: RIPK2 mediates inflammatory signaling by the bacteria‐sensing receptors NOD1 and NOD2. Kinase inhibitors targeting RIPK2 are a proposed strategy to ameliorate NOD‐mediated pathologies. Here, we reveal that RIPK2 kinase activity is dispensable for NOD2 inflammatory signaling and show that RIPK2 inhibitors function instead by antagonizing XIAP‐binding and XIAP‐mediated ubiquitination of RIPK2. We map the XIAP binding site on RIPK2 to the loop between β2 and β3 of the N‐lobe of the kinase, which is in close proximity to the ATP‐binding pocket. Through characterization of a new series of ATP pocket‐binding RIPK2 inhibitors, we identify the molecular features that determine their inhibition of both the RIPK2‐XIAP interaction, and of cellular and in vivo NOD2 signaling. Our study exemplifies how targeting of the ATP‐binding pocket in RIPK2 can be exploited to interfere with the RIPK2‐XIAP interaction for modulation of NOD signaling. Synopsis: Bacteria‐sensing NOD receptors promote inflammatory signalling by stimulating XIAP‐dependent RIPK2 ubiquitination. New RIPK2 kinase inhibitors act by blocking RIPK2‐XIAP binding, thus revealing a strategy to impair NOD signalling independently of RIPK2 kinase activity. RIPK2 kinase activity is dispensable for NOD2 inflammatory signaling. RIPK2 kinase inhibitors block NOD2 signaling by antagonizing RIPK2‐XIAP interaction. Arg36 and Arg41 in RIPK2 kinase domain form a basic patch critical for XIAP interaction. RIPK2 inhibitors occluding the deep pocket behind the ATP‐binding site display potent inhibition of NOD2 signaling. Abstract : A new class of RIPK2 inhibitors dampen inflammatory signalling in a kinase‐independent manner by blocking RIPK2‐XIAP binding and RIPK2 ubiquitination.